Tingkat Kepuasan Mahasiswa Terhadap Menu dan Penyajian Makanan di Asrama AKPER KESDAM IX/Udayana Denpasar - Kadek Putri Wiadnyani; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Satisfaction is the feeling of pleasure or disappointment of a person as a result of a comparison between the perceived and expected product achievement or as a customer response to a discrepancy between the level of prior importance of the actual performance perceived after usage. Important components used to determine the quality of services so that the level of satisfaction can be determined that is, Realybility, Responsive, Assurance, Emphaty, and Tangible. The components assessed in this study include, food menu and food presentation. The type of research used is the type of observational research with cross sectional design. The sample of this research is all of the first grade students who live in Akper Kesdam IX/Udayana Dormitory who have the criteria: registered as a first-degree student Akper Kesdam IX/Udayana Denpasar, male and female, are not ill, willing to be researched. Based on the 72 samples studied, most of them stated that they were not satisfied with the food service provided by the dormitory, with the score of 81.23% satisfaction level, which is still below the standard of satisfaction level ?90%.Keywords : Menu, food presentation, level of satisfaction